1995
DOI: 10.1088/0965-0393/3/1/007
|View full text |Cite
|
Sign up to set email alerts
|

A computer simulation of crystal growth by the traveling-solvent method (TSM): pseudo-steady-state calculations

Abstract: A computer rimulauoo is conducted to smdy single-crystal growth by the travelingsolvent method (TSM) using a pseudo-steady-state model. The model. which ts govemed by momentum, heat, and mass balances in the system. is solved by a Bnite-volume/Newton method.Flow patterns, temperature and solute distributions, and unknown melWsolid interfaces are calculated simultaneously. The model is mainly developed for binary compounds for which the solubility of solvent in solid materials is negtigible. In such a system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…At slightly higher growth rates (not shown), the increased tellurium segregation drives the dissolution interface further downward until it meets the growth interface, representing the maximum growth rate in zero gravity. Qualitatively, these results agree remarkably well with the prior computations by Lan and Yang [19], where a similar effect is seen for cases under microgravity with small solvent volumes.…”
Section: Behavior Without Flowsupporting
confidence: 89%
See 3 more Smart Citations
“…At slightly higher growth rates (not shown), the increased tellurium segregation drives the dissolution interface further downward until it meets the growth interface, representing the maximum growth rate in zero gravity. Qualitatively, these results agree remarkably well with the prior computations by Lan and Yang [19], where a similar effect is seen for cases under microgravity with small solvent volumes.…”
Section: Behavior Without Flowsupporting
confidence: 89%
“…With the exception of the model of Lan and Yang [19], we argue that all of the prior attempts to model this complicated system have been flawed by ignoring important transport phenomena or by inconsistent application of thermodynamic concepts. We address these shortcomings in the model presented here.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Despite the strengths of the THM, it is currently hampered by growth rates that are more than one order of magnitude slower than those routinely employed in Bridgman methods [71,72,[85][86][87][88][89]. Prior models for this process have suggested that morphological instability could readily arise in THM [90,91]. However, these past works did not identify the mechanisms that are responsible for such instability.…”
Section: Growth Rate Limits In the Traveling Heater Methodsmentioning
confidence: 99%